Is the A-Chain the Engine That Drives the Diversity of C1q Functions? Revisiting Its Unique Structure - Ghebrehiwet, Berhane; Kandov, Evelyn; Kishore, Uday; Peerschke, Ellinor I. B. (Frontiers in Immunology, 2018)
The immunopathological functions associated with human C1q are still growing in terms of novelty, diversity, and pathologic relevance. It is, therefore, not surprising that C1q is being recognized as an important molecular bridge between innate and adaptive immunity. The secret of this functional diversity, in turn, resides in the elegant but complex structure of the C1q molecule, which is assembled from three distinct gene products: A, B, and C, each of which has evolved from a separate and unique ancestral gene template. The C1q molecule is made up of 6A, 6B and 6C polypeptide chains, which are held together through strong covalent and non-covalent bonds to form the 18-chain, bouquet-of-flower-like protein that we know today. The assembled C1q protein displays at least two distinct structural and functional regions: the collagen-like region (cC1q), or the globular head region (gC1q), each being capable of driving a diverse range of ligand- or receptor-mediated biological functions. What is most intriguing, however, is the observation that most of the functions appear to be predominantly driven by the A-chain of the molecule, which begs the question: what are the evolutionary modifications or rearrangements that singularly shaped the primordial A-chain gene to become a pluripotent and versatile component of the intact C1q molecule? Here, we revisit and discuss some of the known unique structural and functional features of the A-chain, which may have contributed to its versatility.